Challenges and opportunities for stem cell therapy in patients with chronic kidney disease - Hickson, LaTonya J. (Kidney Int, 2016)
Chronic kidney disease (CKD) is a global healthcare burden affecting billions of individuals worldwide. The kidney has limited regenerative capacity from chronic insults, and for the most common causes of CKD, no effective treatment exists to prevent progression to end-stage kidney failure. Therefore, novel interventions, such as regenerative cell-based therapies, need to be developed for CKD. Given the risk of allosensitization, autologous transplantation of cells to boost regenerative potential is preferred. Therefore, verification of cell function and vitality in CKD patients is imperative. Two cell types have been most commonly applied in regenerative medicine. Endothelial progenitor cells contribute to neovasculogenesis primarily through paracrine angiogenic activity and partly by differentiation into mature endothelial cells in situ. Mesenchymal stem cells also exert paracrine effects, including pro-angiogenic, anti-inflammatory, and anti-fibrotic activity. However, in CKD, multiple factors may contribute to reduced cell function, including older age, coexisting cardiovascular disease, diabetes, chronic inflammatory states, and uremia, which may limit the effectiveness of an autologous cell-based therapy approach. This review highlights current knowledge on stem and progenitor cell function and vitality, aspects of the uremic milieu that may serve as a barrier to therapy, and novel methods to improve stem cell function for potential transplantation.